2010
DOI: 10.1136/qshc.2008.031732
|View full text |Cite
|
Sign up to set email alerts
|

Teamwork training with nursing and medical students: does the method matter? Results of an interinstitutional, interdisciplinary collaboration

Abstract: Objectives The authors conducted a randomised controlled trial of four pedagogical methods commonly used to deliver teamwork training and measured the effects of each method on the acquisition of student teamwork knowledge, skills, and attitudes. Methods The authors recruited 203 senior nursing students and 235 fourth-year medical students (total N¼438) from two major universities for a 1-day interdisciplinary teamwork training course. All participants received a didactic lecture and then were randomly assigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
2
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(105 citation statements)
references
References 15 publications
(13 reference statements)
4
95
2
4
Order By: Relevance
“…Дані літератури свідчать, що ефективність на-дання медичної допомоги, особливо в екстре-них ситуаціях, багато в чому залежить не тільки від окремих призначень лікаря, а більшою мірою від злагоджених дій всієї команди, синхронна та ефективна робота всієї команди дає можливість потенційно уникнути 50 % усіх випадків материн-ської смертності та 75 % усіх випадків смерті при пологах [7,8,11].…”
Section: підготовка медичних кадрівunclassified
“…Дані літератури свідчать, що ефективність на-дання медичної допомоги, особливо в екстре-них ситуаціях, багато в чому залежить не тільки від окремих призначень лікаря, а більшою мірою від злагоджених дій всієї команди, синхронна та ефективна робота всієї команди дає можливість потенційно уникнути 50 % усіх випадків материн-ської смертності та 75 % усіх випадків смерті при пологах [7,8,11].…”
Section: підготовка медичних кадрівunclassified
“…33 Numerous studies have verified that the quality of patient care does improve with increased teamwork among health professionals. [34][35][36][37][38][39] Many health profession educators realize intuitively that their students need multiple instructional events and opportunities to practice interprofessional teamwork. They also need to see their respective faculty members working together in a collegial way in order to appreciate the importance of mutual respect and reliance among health professionals.…”
Section: Postprofessionalmentioning
confidence: 99%
“…A study by Hobgood et al showed that medical and nursing students showed improved attitudes and knowledge about teamwork when participating in IPE, but were unable to show changes in behavior or teamwork skills [12]. Salas and Frush highlighted in BImproving Patient Safety Through Teamwork and Team Training^that any evidence of transfer from knowledge to skills is limited in the literature [13].…”
Section: Introductionmentioning
confidence: 99%